The Relationship of Experimental Jurisprudence to Other Schools of Jurisprudence and to Scientific Method - Frederick K. Beutel (Washington University Law Quarterly, 1971)
It might be worthwhile to pause for a bit to discuss the relationship of Experimental Jurisprudence to the many other schools of jurisprudence which have existed from time to time. It has also an important relation to the expansion of the scientific method into the literature and practice of social control through law. There is no need here to go into a detailed scholarly discussion of the history of jurisprudential thought. This has been done so superbly by Stone and Pound that a repetition of the process would be superfluous. However, a general discussion of its methods in relation to other well known types of thought and action in the field of philosophy and practice in government might prove useful to a better understanding of Experimental Jurisprudence.
Keywords: Jurisprudence